Pregunta
upstudy study bank question image url

(c) Simplify the following: \( \begin{array}{lll}\text { (1) } \frac{3^{2 x+1}}{3^{2 x}} & \text { (2) } \frac{2^{x+5}}{2^{x+2}} & \text { (3) } \frac{5^{n+4}}{5^{m+5}} \\ \text { (4) } \frac{2^{3 x+5}}{2^{3 x+9}} & \text { (5) } \frac{6^{4 x-2}}{6^{4 x-4}} & \text { (6) } \frac{4^{n}}{2^{2 n-3}} \\ \text { (7) } \frac{7^{2 x-1}}{49^{x-1}} & \text { (8) } \frac{9^{x+1}}{3^{2 x} \cdot 81} & \text { (9) }-\frac{16^{p-3}}{8^{p-4}} \\ \text { (10) } \frac{5^{x} \cdot 25^{x-1}}{5 \cdot 125^{x}} & \text { (11) } \frac{9^{a} \cdot 4^{a-1}}{3^{2 a-1} \cdot 2^{2 a}} & \text { (12) } \frac{36^{x+2}}{6^{2 x+5}} \\ \text { (13) } \frac{50^{x+1}}{2^{x+1}} 25^{x+2} & \text { (14) } \frac{5 \cdot 45^{y}}{9^{y} \cdot 5^{y+2}} & \text { (15) } \frac{18^{x} \cdot 8^{x-1}}{9^{x+1} \cdot 4^{2 x-1}}\end{array} \)

Ask by Garrett Munoz. in South Africa
Feb 24,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

Here are the simplified results for each expression: 1. \( 3 \) 2. \( 8 \) 3. \( 5^{n-1-m} \) 4. \( \frac{1}{16} \) 5. \( 36 \) 6. \( 8 \) 7. \( 7 \) 8. \( \frac{1}{9} \) 9. \( -2^{p} \) 10. \( \frac{1}{125} \) 11. \( \frac{3}{4} \) 12. \( \frac{1}{6} \) 13. \( \frac{1}{25} \) 14. \( \frac{1}{5} \) 15. \( \frac{18^{x} \cdot 8^{x-1}}{9^{x+1} \cdot 4^{2x-1}} \)

Solución

Simplify the expression by following steps: - step0: Solution: \(\frac{7^{2x-1}}{49^{x-1}}\) - step1: Calculate: \(\frac{7^{2x-1}}{\left(7^{2}\right)^{x-1}}\) - step2: Calculate: \(\frac{7^{2x-1}}{7^{2x-2}}\) - step3: Calculate: \(7\) Calculate or simplify the expression \( \frac{9^{a} \cdot 4^{a-1}}{3^{2 a-1} \cdot 2^{2 a}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{9^{a}\times 4^{a-1}}{3^{2a-1}\times 2^{2a}}\) - step1: Factor the expression: \(\frac{3^{2a}\times 4^{a-1}}{3^{2a-1}\times 2^{2a}}\) - step2: Reduce the fraction: \(\frac{3\times 4^{a-1}}{2^{2a}}\) - step3: Factor the expression: \(\frac{3\times 2^{2a-2}}{2^{2a}}\) - step4: Reduce the fraction: \(\frac{3}{2^{2}}\) - step5: Evaluate the power: \(\frac{3}{4}\) Calculate or simplify the expression \( \frac{18^{x} \cdot 8^{x-1}}{9^{x+1} \cdot 4^{2 x-1}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{18^{x}\times 8^{x-1}}{9^{x+1}\times 4^{2x-1}}\) - step1: Factor the expression: \(\frac{9^{x}\times 2^{x}\times 8^{x-1}}{9^{x+1}\times 4^{2x-1}}\) - step2: Reduce the fraction: \(\frac{2^{x}\times 8^{x-1}}{9\times 4^{2x-1}}\) - step3: Factor the expression: \(\frac{2^{x}\times 8^{x-1}}{9\times 2^{4x-2}}\) - step4: Reduce the fraction: \(\frac{8^{x-1}}{9\times 2^{3x-2}}\) - step5: Factor the expression: \(\frac{2^{3x-3}}{9\times 2^{3x-2}}\) - step6: Reduce the fraction: \(\frac{1}{9\times 2}\) - step7: Calculate: \(\frac{1}{18}\) Calculate or simplify the expression \( \frac{5^{n+4}}{5^{m+5}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{5^{n+4}}{5^{m+5}}\) - step1: Multiply by \(a^{-n}:\) \(5^{n+4}\times 5^{-\left(m+5\right)}\) - step2: Calculate: \(5^{n+4}\times 5^{-m-5}\) - step3: Multiply: \(5^{n+4-m-5}\) - step4: Calculate: \(5^{n-1-m}\) Calculate or simplify the expression \( \frac{2^{x+5}}{2^{x+2}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{2^{x+5}}{2^{x+2}}\) - step1: Multiply by \(a^{-n}:\) \(2^{x+5}\times 2^{-\left(x+2\right)}\) - step2: Calculate: \(2^{x+5}\times 2^{-x-2}\) - step3: Multiply: \(2^{x+5-x-2}\) - step4: Calculate: \(2^{3}\) - step5: Evaluate the power: \(8\) Calculate or simplify the expression \( \frac{3^{2 x+1}}{3^{2 x}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{3^{2x+1}}{3^{2x}}\) - step1: Multiply by \(a^{-n}:\) \(3^{2x+1}\times 3^{-2x}\) - step2: Multiply: \(3^{2x+1-2x}\) - step3: Calculate: \(3\) Calculate or simplify the expression \( \frac{6^{4 x-2}}{6^{4 x-4}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{6^{4x-2}}{6^{4x-4}}\) - step1: Multiply by \(a^{-n}:\) \(6^{4x-2}\times 6^{-\left(4x-4\right)}\) - step2: Calculate: \(6^{4x-2}\times 6^{-4x+4}\) - step3: Multiply: \(6^{4x-2-4x+4}\) - step4: Calculate: \(6^{2}\) - step5: Evaluate the power: \(36\) Calculate or simplify the expression \( \frac{4^{n}}{2^{2 n-3}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{4^{n}}{2^{2n-3}}\) - step1: Calculate: \(\frac{\left(2^{2}\right)^{n}}{2^{2n-3}}\) - step2: Calculate: \(\frac{2^{2n}}{2^{2n-3}}\) - step3: Calculate: \(2^{3}\) Calculate or simplify the expression \( \frac{2^{3 x+5}}{2^{3 x+9}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{2^{3x+5}}{2^{3x+9}}\) - step1: Multiply by \(a^{-n}:\) \(2^{3x+5}\times 2^{-\left(3x+9\right)}\) - step2: Calculate: \(2^{3x+5}\times 2^{-3x-9}\) - step3: Multiply: \(2^{3x+5-3x-9}\) - step4: Calculate: \(2^{-4}\) - step5: Express with a positive exponent: \(\frac{1}{2^{4}}\) - step6: Evaluate the power: \(\frac{1}{16}\) Calculate or simplify the expression \( \frac{50^{x+1}}{2^{x+1} \cdot 25^{x+2}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{50^{x+1}}{2^{x+1}\times 25^{x+2}}\) - step1: Factor the expression: \(\frac{2^{x+1}\times 25^{x+1}}{2^{x+1}\times 25^{x+2}}\) - step2: Reduce the fraction: \(\frac{25^{x+1}}{25^{x+2}}\) - step3: Divide the numbers: \(\frac{1}{25^{x+2-\left(x+1\right)}}\) - step4: Subtract the terms: \(\frac{1}{25^{1}}\) - step5: Simplify: \(\frac{1}{25}\) Calculate or simplify the expression \( \frac{36^{x+2}}{6^{2 x+5}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{36^{x+2}}{6^{2x+5}}\) - step1: Calculate: \(\frac{\left(6^{2}\right)^{x+2}}{6^{2x+5}}\) - step2: Calculate: \(\frac{6^{2x+4}}{6^{2x+5}}\) - step3: Calculate: \(6^{-1}\) Calculate or simplify the expression \( -\frac{16^{p-3}}{8^{p-4}} \). Simplify the expression by following steps: - step0: Solution: \(-\frac{16^{p-3}}{8^{p-4}}\) - step1: Calculate: \(-2^{p}\) Calculate or simplify the expression \( \frac{9^{x+1}}{3^{2 x} \cdot 81} \). Simplify the expression by following steps: - step0: Solution: \(\frac{9^{x+1}}{3^{2x}\times 81}\) - step1: Multiply: \(\frac{9^{x+1}}{3^{2x+4}}\) - step2: Factor the expression: \(\frac{3^{2x+2}}{3^{2x+4}}\) - step3: Divide the numbers: \(\frac{1}{3^{2x+4-\left(2x+2\right)}}\) - step4: Subtract the terms: \(\frac{1}{3^{2}}\) - step5: Evaluate the power: \(\frac{1}{9}\) Calculate or simplify the expression \( \frac{5 \cdot 45^{y}}{9^{y} \cdot 5^{y+2}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{5\times 45^{y}}{9^{y}\times 5^{y+2}}\) - step1: Multiply by \(a^{-n}:\) \(\frac{5\times 45^{y}\times 5^{-\left(y+2\right)}}{9^{y}}\) - step2: Calculate: \(\frac{5\times 45^{y}\times 5^{-y-2}}{9^{y}}\) - step3: Multiply: \(\frac{5^{-1-y}\times 45^{y}}{9^{y}}\) - step4: Factor the expression: \(\frac{5^{-1-y}\times 9^{y}\times 5^{y}}{9^{y}}\) - step5: Reduce the fraction: \(5^{-1-y}\times 5^{y}\) - step6: Express with a positive exponent: \(\frac{1}{5^{1+y}}\times 5^{y}\) - step7: Rewrite the expression: \(\frac{5^{y}}{5^{1+y}}\) - step8: Calculate: \(5^{y-\left(1+y\right)}\) - step9: Calculate: \(5^{-1}\) - step10: Express with a positive exponent: \(\frac{1}{5}\) Calculate or simplify the expression \( \frac{5^{x} \cdot 25^{x-1}}{5 \cdot 125^{x}} \). Simplify the expression by following steps: - step0: Solution: \(\frac{5^{x}\times 25^{x-1}}{5\times 125^{x}}\) - step1: Multiply by \(a^{-n}:\) \(\frac{5^{x}\times 25^{x-1}\times 5^{-1}}{125^{x}}\) - step2: Multiply: \(\frac{5^{3x-3}}{125^{x}}\) - step3: Factor the expression: \(\frac{5^{3x-3}}{5^{3x}}\) - step4: Divide the numbers: \(\frac{1}{5^{3x-\left(3x-3\right)}}\) - step5: Subtract the terms: \(\frac{1}{5^{3}}\) - step6: Evaluate the power: \(\frac{1}{125}\) Here are the simplified results for each expression: 1. \( \frac{3^{2x+1}}{3^{2x}} = 3^{(2x+1) - 2x} = 3^1 = 3 \) 2. \( \frac{2^{x+5}}{2^{x+2}} = 2^{(x+5) - (x+2)} = 2^{3} = 8 \) 3. \( \frac{5^{n+4}}{5^{m+5}} = 5^{(n+4) - (m+5)} = 5^{n-1-m} \) 4. \( \frac{2^{3x+5}}{2^{3x+9}} = 2^{(3x+5) - (3x+9)} = 2^{-4} = \frac{1}{16} \) 5. \( \frac{6^{4x-2}}{6^{4x-4}} = 6^{(4x-2) - (4x-4)} = 6^{2} = 36 \) 6. \( \frac{4^{n}}{2^{2n-3}} = \frac{(2^2)^{n}}{2^{2n-3}} = \frac{2^{2n}}{2^{2n-3}} = 2^{3} = 8 \) 7. \( \frac{7^{2x-1}}{49^{x-1}} = \frac{7^{2x-1}}{(7^2)^{x-1}} = \frac{7^{2x-1}}{7^{2(x-1)}} = 7^{(2x-1) - 2(x-1)} = 7^{2x-1-2x+2} = 7^{1} = 7 \) 8. \( \frac{9^{x+1}}{3^{2x} \cdot 81} = \frac{(3^2)^{x+1}}{3^{2x} \cdot 3^4} = \frac{3^{2(x+1)}}{3^{2x} \cdot 3^4} = \frac{3^{2x+2}}{3^{2x+4}} = 3^{(2x+2) - (2x+4)} = 3^{-2} = \frac{1}{9} \) 9. \( -\frac{16^{p-3}}{8^{p-4}} = -\frac{(2^4)^{p-3}}{(2^3)^{p-4}} = -\frac{2^{4(p-3)}}{2^{3(p-4)}} = -2^{4p-12 - 3p + 12} = -2^{p} \) 10. \( \frac{5^{x} \cdot 25^{x-1}}{5 \cdot 125^{x}} = \frac{5^{x} \cdot (5^2)^{x-1}}{5 \cdot (5^3)^{x}} = \frac{5^{x} \cdot 5^{2x-2}}{5^{1+3x}} = \frac{5^{x + 2x - 2}}{5^{3x + 1}} = \frac{5^{3x - 2}}{5^{3x + 1}} = 5^{(3x - 2) - (3x + 1)} = 5^{-3} = \frac{1}{125} \) 11. \( \frac{9^{a} \cdot 4^{a-1}}{3^{2a-1} \cdot 2^{2a}} = \frac{(3^2)^{a} \cdot (2^2)^{a-1}}{3^{2a-1} \cdot 2^{2a}} = \frac{3^{2a} \cdot 2^{2a-2}}{3^{2a-1} \cdot 2^{2a}} = \frac{3^{2a} \cdot 2^{2a-2}}{3^{2a-1} \cdot 2^{2a}} = \frac{3^{2a}}{3^{2a-1}} \cdot \frac{2^{2a-2}}{2^{2a}} = 3^{1} \cdot 2^{-2} = \frac{3}{4} \) 12. \( \frac{36^{x+2}}{6^{2x+5}} = \frac{(6^2)^{x+2}}{6^{2x+5}} = \frac{6^{2(x+2)}}{6^{2x+5}} = 6^{2x+4 - (2x+5)} = 6^{-1} = \frac{1}{6} \) 13. \( \frac{50^{x+1}}{2^{x+1} \cdot 25^{x+2}} = \frac{(2 \cdot 25)^{x+1}}{2^{x+1} \cdot (5^2)^{x+2}} = \frac{2^{x+1} \cdot 5^{2(x+1)}}{2^{x+1} \cdot 5^{2x+4}} = \frac{5^{2(x+1)}}{5^{2x+4}} = 5^{2x+2 - (2x+4)} = 5^{-2} = \frac{1}{25} \) 14. \( \frac{5 \cdot 45^{y}}{9^{y} \cdot 5^{y+2}} = \frac{5 \cdot (5 \cdot 9)^{y}}{9^{y} \cdot 5^{y+2}} = \frac{5^{1+y} \cdot 9^{y}}{9^{y} \cdot 5^{y+2}} = \frac{5^{1+y}}{5^{y+2}} = 5^{1+y - (y+2)} = 5^{-1} = \frac{1}{5} \) 15. \( \frac{18^{x} \cdot 8^{x-1}}{9^{x+1} \cdot 4^{2x-1}} = \frac{(2 \cdot 9)^{x} \cdot (2^3)^{x-1}}{(3^2)^{x+1} \cdot (2^2)^{2x-1}} = \frac

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To simplify these expressions, you'll mainly want to take advantage of the laws of exponents. Using the property \( \frac{a^m}{a^n} = a^{m-n} \) and the fact that other bases can often be expressed in terms of common bases will make this much simpler. 1. \( (1) \frac{3^{2x+1}}{3^{2x}} = 3^{(2x+1) - (2x)} = 3^1 = 3 \) 2. \( (2) \frac{2^{x+5}}{2^{x+2}} = 2^{(x+5)-(x+2)} = 2^3 = 8 \) 3. \( (3) \frac{5^{n+4}}{5^{m+5}} = 5^{(n+4)-(m+5)} = 5^{n-m-1} \) 4. \( (4) \frac{2^{3x+5}}{2^{3x+9}} = 2^{(3x+5)-(3x+9)} = 2^{-4} = \frac{1}{16} \) 5. \( (5) \frac{6^{4x-2}}{6^{4x-4}} = 6^{(4x-2)-(4x-4)} = 6^2 = 36 \) 6. \( (6) \frac{4^n}{2^{2n-3}} = \frac{(2^2)^n}{2^{2n-3}} = \frac{2^{2n}}{2^{2n-3}} = 2^{2n-(2n-3)} = 2^3 = 8 \) 7. \( (7) \frac{7^{2x-1}}{49^{x-1}} = \frac{7^{2x-1}}{7^{2(x-1)}} = 7^{2x-1-2x+2} = 7^{1} = 7 \) 8. \( (8) \frac{9^{x+1}}{3^{2x} \cdot 81} = \frac{9^{x+1}}{3^{2x} \cdot 3^4} = \frac{3^{2(x+1)}}{3^{2x+4}} = 3^{2x+2-2x-4} = 3^{-2} = \frac{1}{9} \) 9. \( (9) -\frac{16^{p-3}}{8^{p-4}} = -\frac{(2^4)^{p-3}}{(2^3)^{p-4}} = -\frac{2^{4(p-3)}}{2^{3(p-4)}} = -2^{4p-12-3p+12} = -2^{p} \) 10. \( (10) \frac{5^x \cdot 25^{x-1}}{5 \cdot 125^x} = \frac{5^x \cdot (5^2)^{x-1}}{5 \cdot (5^3)^{x}} = \frac{5^x \cdot 5^{2x-2}}{5^{1+3x}} = \frac{5^{3x-2}}{5^{3x+1}} = 5^{3x-2-3x-1} = 5^{-3} = \frac{1}{125} \) 11. \( (11) \frac{9^{a} \cdot 4^{a-1}}{3^{2a-1} \cdot 2^{2a}} = \frac{(3^2)^{a} \cdot (2^2)^{a-1}}{3^{2a-1} \cdot 2^{2a}} = \frac{3^{2a} \cdot 2^{2a-2}}{3^{2a-1} \cdot 2^{2a}} = \frac{3^{2a} \cdot 2^{2a-2}}{3^{2a-1} \cdot 2^{2a}} = 3^{1} \cdot 2^{-2} = \frac{3}{4} \) 12. \( (12) \frac{36^{x+2}}{6^{2x+5}} = \frac{(6^2)^{x+2}}{6^{2

preguntas relacionadas

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad